SUPERVISORS’ BEHAVIOR IN STUDENT RESEARCH ENGAGEMENT: GUIDANCE AND OVERSIGHT - Narreen Hashmi; Zainab Ajab Mohideen (Policy Journal of Social Science Review, 2026)
This study examines how supervisors’ behavior shapes student research engagement, with particular focus on guidance, communication, and oversight practices. Rather than treating supervision as a purely administrative task, this study views it as an interactive process that directly influences students’ learning and research development. The findings suggest that supervisors play a dual role: they guide students academically while also ensuring that research is conducted in a responsible and ethical manner. Students benefit most when supervisors provide clear direction, timely feedback, and consistent support throughout the research process. The study further emphasizes that effective supervision is not only dependent on individual effort but also on institutional support. Strengthening mentoring practices and providing professional development opportunities for supervisors can significantly enhance research outcomes. Overall, this study contributes to a clearer understanding of how supervisory behavior can improve both student engagement and research quality. Keywords: Supervision, Supervisors, Supervisor behavior, Research students, Research engagement